2008
DOI: 10.1021/jp804334f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bond-Driven Assembly of Thin Multiwalled Carbon Nanotubes

Abstract: We report on the formation of the assembled bundle structure of thin multiwalled carbon nanotubes (t-MWNTs) modified with hydroxyl groups, which was assisted by the intertube hydrogen bonding interaction. To achieve this, the t-MWNTs were first functionalized with hydroxide (t-MWNT-OH) by reflux in hydrogen peroxide. For the comparison, the carboxyl-modified t-MWNTs (t-MWNTs-COOH) were prepared by nitric acid treatment as a control sample. After filtration of a functionalized t-MWNT solution, the flexible t-MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…In the FTIR spectrum of MWNT–OH, shown in Figure 1, the CO and CO stretching vibrations of ester groups shifted from 1722 cm −1 and 1182 cm −1 to 1738 cm −1 and 1203 cm −1 , respectively, as compared with the same transitions in Figure 1(B) 35, 36. This observation confirmed that the COCl group of MWNT–COCl reacted with ethylene glycol to form MWNT–OH.…”
Section: Resultssupporting
confidence: 61%
“…In the FTIR spectrum of MWNT–OH, shown in Figure 1, the CO and CO stretching vibrations of ester groups shifted from 1722 cm −1 and 1182 cm −1 to 1738 cm −1 and 1203 cm −1 , respectively, as compared with the same transitions in Figure 1(B) 35, 36. This observation confirmed that the COCl group of MWNT–COCl reacted with ethylene glycol to form MWNT–OH.…”
Section: Resultssupporting
confidence: 61%
“…35,36 This observation confirmed that the ACOCl group of MWNT-COCl reacted with ethylene glycol to form MWNT-OH. The hydroxyl stretching band appeared as a strong, broad band at 3385 cm À1 in crude MWNTs but shifted to 3441 cm À1 and 3426 cm À1 in samples of MWNTÀCOOH and MWNTÀOH, respectively.…”
supporting
confidence: 58%
“…This implies that the higher stretching force in HS makes the polymer chains more ordered, resulting in breaking the semi-crystalline structure. Second, hydrogen bonding between the ester groups, which were formed in the polymer chains and in the carboxylic acid groups on the CNTs by pre-treatment with acid, could disrupt the crystallinity of the PVAc3940. Thus, these results emphasize the significance of understanding the interaction in the composite.…”
Section: Resultsmentioning
confidence: 91%